1996
DOI: 10.1111/j.1476-5381.1996.tb15557.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide synthesis by NG‐nitro‐L‐arginine methyl ester (L‐NAME): requirement for bioactivation to the free acid, NG‐nitro‐L‐arginine

Abstract: 1 The L-arginine derivatives N0-nitro-L-arginine (L-NOARG) and NG-nitro-L-arginine methyl ester (L-NAME) have been widely used to inhibit constitutive NO synthase (NOS) in different biological systems. This work was carried out to investigate whether L-NAME is a direct inhibitor of NOS or requires preceding hydrolytic bioactivation to L-NOARG for inhibition of the enzyme. 2 A bolus of L-NAME and L-NOARG (0.25 Mmol) increased coronary perfusion pressure of rat isolated hearts to the same extent (21 +0.8 mmHg; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
132
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(147 citation statements)
references
References 46 publications
8
132
0
7
Order By: Relevance
“…L-NAME has been shown to inhibit the synthesis of NO in the endothelium (Rees et al, 1990;Pfeiffer et al, 1996), and such inhibition has been reported to enhance vascular smooth muscle contraction (Martin et al, 1986;Alosachie and Godfraind, 1988;Osugi et al, 1990;Kaneko and Sunano, 1993). We have also observed that EDR of the aorta and of the carotid and iliac arteries from L-NAME-treated rats was impaired (Sekiguchi et al, 2001).…”
Section: Discussionsupporting
confidence: 55%
“…L-NAME has been shown to inhibit the synthesis of NO in the endothelium (Rees et al, 1990;Pfeiffer et al, 1996), and such inhibition has been reported to enhance vascular smooth muscle contraction (Martin et al, 1986;Alosachie and Godfraind, 1988;Osugi et al, 1990;Kaneko and Sunano, 1993). We have also observed that EDR of the aorta and of the carotid and iliac arteries from L-NAME-treated rats was impaired (Sekiguchi et al, 2001).…”
Section: Discussionsupporting
confidence: 55%
“…The effect of ADMA was similar to that of L-NAME, a known inhibitor of NOS. 21 ADMA induced a decrease in NOx levels, suggesting that ADMA induces intrahepatic endothelial dysfunction by inhibiting NOS. When ADMA was administrated together with L-NAME, a synergistic increase in perfusion pressure-or paradoxical vasoconstriction-occurred, which was associated with a further decrease in NOx levels.…”
Section: Discussionmentioning
confidence: 90%
“…L-NAME is an inactive prodrug that upon hydrolization is bioactivated to N G -nitro-L-arginine, a direct inhibitor of NOS. 21 The response to cumulative doses of acetylcholine was expressed as percent change in perfusion pressure, as previously described. 5,7 Determination of Dimethylarginines and NOx.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous studies, the blood pressure effect persisted after discontinuation of L-NAME, consistent with conversion of L-NAME to a long-acting active metabolite L-N G -nitro-Larginine. 22 L-NAME decreased heart rate, most likely because of stimulation of the baroreflex. Interestingly, although 1 month of pretreatment with oral L-arginine attenuated the peak blood pressure response to L-NAME, it did not abolish this pressor response.…”
Section: Discussionmentioning
confidence: 93%